Influência do polímero utilizado como aglomerante em eletrodos revestidos básicos sobre a formação de ferrita acicular no metal de solda - Claudio Turani Vaz (2014)
Shielded metal arc welding were one of the most important processes along part of the twenty century. Nowadays, where there are most productive welding processes, the basic covered electrodes are largely used at high responsibility services. However, the coating moisture absorption is a problem to overcome. Underwater wet welding studies showed the availability to replace the traditional binders (silicates) by polymers on the electrode production. The use of this technology on conventional basic electrodes presented satisfactory results. The main goal, to make a moisture resistant covered electrode with low diffusible hydrogen content weld metal, was reached. Furthermore, was possible to obtain a weld metal mainly composed by acicular ferrite. The main objective of this thesis was to explore the microstructural differences and evaluate the polymer influence on it. Comparison between the weld metal microstructure obtained by polymer agglomerated electrodes and provided in the literature with similar chemical composition showed strong differences. The study of conditions used to obtain these weld metals did not justified the observed differences. On the other hand, the evaluation of residual chemical elements presented some differences, mainly nitrogen content, which could justify it. The influence of other chemical elements could not be disregarded. However, they had a complementary function. The evaluation of polymer agglomerated and E7018 class electrodes operational characteristics identified how the polymer influences the weld metal nitrogen content. A comparison between wire, metallic droplets and weld metal nitrogen content confirmed the absorption during metallic transfer, thus it came from atmosphere contamination. The experiments showed that less nitrogen content can be related to most effective shielding and to metallic transfer mode changes. The high carbon content on the weld metal produced by electrodes with polymer indicated a rich carbon atmosphere. The slag X-Ray Diffraction indicated changes on the atmosphere which involves the arc. The formed droplet morphology, average droplet size and voltage monitoring during welding confirmed the metallic transfer changes.